How Do Industrial Enterprises Respond to Policy Reforms? Supply Response in Cameroon - Tybut, J.; Gauthier, B.; Barba-Navaretti, G.; De Melo, J. (World Bank, Washington, DC, 2012)
Between 1986 and 1993, adverse terms of trade shocks combined with a rigidly pegged nominal exchange rate and various domestic distortions to reduce Cameroon's per capita income by roughly 50 percent. Though major policy reforms were slow to come, the Chartered Financial Analyst (CFA) franc was finally devalued in 1994. A study conducted on more than 200 manufacturing enterprises in Cameroon, before and after devaluation and reforms. The 1994 devaluation of the CFA franc dramatically increased the price of imported intermediate goods. This increase in costs was large enough to substantially reduce profits at some firms, particularly those that were heavily dependent upon imported intermediates. However, at firms using domestic inputs, and especially at firms producing exportable goods, the increase in input costs was more than offset by rising output prices, and profit margins improved. Labor costs rose by roughly the rate of inflation overall, so they went up relative to output prices in non-traded goods sectors, and fell relative to output prices in others.